LEADER MEMBER EXCHANGE SEBAGAI MEDIASI ANTARA KEPRIBADIAN PROAKTIF DAN KEPUASAN KERJA STUDI PADA PERUSAHAAN MALANG STRUDEL - iqbal Ramadhani Fuadiputra (Jurnal Manajemen, 2020)
The research was done due to employee satisfaction which should be facilitated by the proximity of the leader as mediation because of the closeness of the leader and proactive personality existing employee identification expectations related to job satisfaction of the workers will increase. In this study, the proximity of leadership serves as a mediating variable. Malang Strudel used as an object of research is based on the continued development of Strudel Malang in Malang area. As well as the tightness of growth and development in the food business impact capabilities demand tightness employees to have a proactive personality that serves to complete the work of the company. High target of company makes leaders must also engage with employees in order to have an impact on employee satisfaction. Respondents for the study were all employees of Malang Strudel (70 people). The research variables are described in the questionnaire that will be distributed to the respondents for this study using saturated sample and data will be processed using smart analysis of PLS. Based on research conducted showed that employees Malang Strudel are employees who have a positive personality. This is indicated by the value of the three variables (proactive personality, job satisfaction and the closeness of the relationship between leaders and employees) high. Keywords: Leader Member Exhange; Proactive Personality; Job Satisfaction